EL IMPACTO DE LAS INVERSIONES EN SALUD Y SU CONTROL EN LA MORTALIDAD INFANTIL, PERIODO 1990 – 2014” - Castillo Namicela, Guido Fernando (2016)
One of the biggest problems that humanity faces is related to the control and reduction of infant mortality rate, for which policies have been developed by governments of all countries considered important to know the variables that influence the mortality rate in order to properly implement these policies in our country, hence the need for this work "Analyze the impact of investments in health and its effect on infant mortality in the city of Loja, using correlation analysis and thus provide the necessary inputs for the corresponding analysis in the year 1990 - 2014". Justifies develop this work because it is considered essential to know the variables that influence infant mortality allowing effective solutions. The research is descriptive, focused on knowing the reality of the phenomenon under study, deductive, analytical and statistical methods were used. The analyzed data show a continuing downward trend in fertility rates in women from an average of 3.76 in 1990 to 2.22 in 2014 ; according to the results of applied if the fertility rate decreases 1% model the infant mortality rate decreases by about 5.94 per thousand births; The per capita income for the results show that increasing the per capita income on a dollar decreases in infant mortality 0.005 % per thousand live births. Investment in improving hospital infrastructure, medical preparation is also important, the model developed confirms that if investment in health infrastructure is increased by one million infant mortality decreased by 1.24 per thousand births. Keywords: infant mortality , fertility, multicollinearity , heteroscedasticity , autocorrelation , Pearson correlation coefficient , autoregressive scheme homoscedasticity , covariance , collinear variable, Jarque Bera test and the City of Loja